Role of Beliefs in Predicting Smoking Behaviour: a Study of Comparative Optimism in Cameroonian Adolescents - Bala, Fabrice Etoundi; Mvessomba, Edouard Adrien; Ngah Essomba, Helene Chantal (European Scientific Journal, ESJ, 2022)
The objective of this study was to examine the influence of comparative optimism on the intention to use tobacco among 244 Cameroonian adolescent students. The sample consisted of girls (n=110) and boys (n=134) aged between 14 and 25 in secondary school. Participants were selected using a purposive sampling technique. The study relied primarily on the theory of planned behaviour to highlight the mechanisms that link beliefs to behavioural intentions. Data were collected from a self-administered composite questionnaire consisting of the comparative optimism scale and the risk-taking scale measuring intention to use tobacco inspired by the theory of planned behaviour. The results obtained after correlation analysis and regression showed that the illusion of vulnerability elicits the intention to use tobacco through attitude (r= -.141, p<0.05), descriptive norms (r=.204, p<0.01), and injunctive norms (r=.132, p<0.05). In addition, the illusion of vulnerability also appears as a predictor of the intention to use tobacco. These results confirm the harmful nature of overly optimistic beliefs about protective behaviours. The implications of the optimism bias for perceived vulnerability are discussed in the light of reference theories and from previous work on the effect of optimistic beliefs on protective behaviour.